(-)-Epigallocatechin-3-Gallate (EGCG) Modulates the Composition of the Gut Microbiota to Protect Against Radiation-Induced Intestinal Injury in Mice - Cai, Shang; Xie, Li-Wei; Xu, Jia-Yu; Zhou, Hao; Yang, Chao; Tang, Lin-Feng; Tian, Ye; Li, Ming (Frontiers in Oncology, 2022)
The high radiosensitivity of the intestinal epithelium limits the outcomes of radiotherapy against abdominal malignancies, which results in poor prognosis. Currently, no effective prophylactic or therapeutic strategy is available to mitigate radiation toxicity in the intestine. Our previous study revealed that the green tea polyphenol (-)-epigallocatechin-3-gallate (EGCG) attenuates radiation-induced intestinal injury (RIII). The aim of the present study was to determine the effect of EGCG on the intestinal flora of irradiated mice. EGCG administration reduced radiation-induced intestinal mucosal injury, and significantly increased the number of Lgr5+ intestinal stem cells (ISCs) and Ki67+ crypt cells. In addition, EGCG reversed radiation-induced gut dysbiosis, restored the Firmicutes/Bacteroidetes ratio, and increased the abundance of beneficial bacteria. Our findings provide novel insight into EGCG-mediated remission of RIII, revealing that EGCG could be a potential modulator of gut microbiota to prevent and treat RIII.